The Effect of Employment Protection on Worker Effort: A Comparison of Absenteeism During and After Probation - Andrea Ichino; Regina T. Riphahn (Institute for the Study of Labor (IZA), 2001)
Employment protection systems are known to generate significant distortions in firms? hiring and firing decisions. We know much less about the impact of these regulations on worker effort. The goal of this paper is to fill in this gap and in particular to assess whether the provision of employment protection induces less effort among workers in the form of absenteeism. Our analysis is based on weekly observations for the 858 white collar workers hired by a large Italian bank between January 1993 and February 1995. These workers begin to be protected against firing only after the twelfth week of tenure and we observe them for one year. We show that the number of days of absence per week more than doubles once employment protection is granted, thus confirming what is suggested by our theoretical model and what is typically assumed in the literature. We also discuss how this evidence can be used to estimate what the absenteeism rate would be in Italy if employment protection were eliminated.
Keywords: J24; J31; J41; M50; 330; Probation; employment protection; absenteeism; worker effort; Kündigungsschutz; Leistungsmotivation; Fehlzeit; Bank; Theorie; Italien; Probezeit